1996
DOI: 10.1111/j.1574-6968.1996.tb08172.x
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug resistance in enteric and other Gram-negative bacteria

Abstract: In Gram-negative bacteria, multidrug resistance is a term that is used to describe mechanisms of resistance by chromosomal genes that are activated by induction or mutation caused by the stress of exposure to antibiotics in natural and clinical environments. Unlike plasmid-borne resistance genes, there is no alteration or degradation of drugs or need for genetic transfer. Exposure to a single drug leads to cross-resistance to many other structurally and functionally unrelated drugs. The only mechanism identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(71 citation statements)
references
References 42 publications
2
69
0
Order By: Relevance
“…In a previous study we monitored tributyltin (TBT) pollution and TBT-resistant bacteria and observed no correlation between the two 18) , suggesting that selective pressures other than TBT selected for resistant bacteria. In the case of TC resistance, it is known that treatment with a single drug leads to resistance of that drug and cross-resistance to other drugs 4) . Furthermore, a recent study reported that resistance to metals and TC are linked 16) .…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study we monitored tributyltin (TBT) pollution and TBT-resistant bacteria and observed no correlation between the two 18) , suggesting that selective pressures other than TBT selected for resistant bacteria. In the case of TC resistance, it is known that treatment with a single drug leads to resistance of that drug and cross-resistance to other drugs 4) . Furthermore, a recent study reported that resistance to metals and TC are linked 16) .…”
Section: Resultsmentioning
confidence: 99%
“…The first kind of pleiotropic effect can be named cross-infectivity by analogy to cross-resistance of microbes, insects, or weeds to different (bio)chemical compounds in a medical or agricultural context (35)(36)(37)(38)(39). It can be defined as the effect of a single mutational event which leads to the breakdown of at least two plant resistance genes or alleles, an initial one, which exerts selection pressure on the pathogen population leading to the fixation of an RB mutation, and a second one, which does not play any role in the fixation of the RB mutation.…”
Section: Discussionmentioning
confidence: 99%
“…The AcrAB-TolC system of E. coli is one of the best-characterized MDR transporters (85,86). The phenotype caused by its deletion was already described in 1965 as a locus disruption which renders E. coli sensitive to basic dyes, detergents, and hydrophobic antibiotics (37). This system consists of AcrA, the membrane fusion protein; AcrB, a transporter of the RND family; and TolC, the outer membrane protein.…”
Section: Abc-type Mdr Transport Systems In Gram-negative Bacteriamentioning
confidence: 99%